Teoria dos conjuntos fuzzy: da simulação ao letramento para alunos do ensino médio - Sant'Anna, Camila dos Santos (2017)
In this work we present a research carried out in the classroom with the objective of treating subjective questions through the Fuzzy Logic with students of the third year of high school. We begin with the study of the basic concepts of Fuzzy Set Theory and systems based on fuzzy rules. Then, aiming at an application, we developed a fuzzy system to evaluate the risk of an individual developing type 2diabetes, from risk factors. Finally, we propose a didactic sequence to the students, through a questionnaire and a lecture given by the author. The results of the research are presented and, if on the one hand they indicate the difficulty of the students with the fuzzy reasoning, on the other hand, demonstrated the interest and the role of Logica Fuzzy, and therefore, of Mathematics in solving problems of our daily life.